2011
DOI: 10.2310/7750.2010.09033
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologic Manifestations of Sjögren Syndrome

Abstract: Sjögren syndrome (SS) is a chronic autoimmune inflammatory disease that involves primarily the exocrine glands, resulting in their functional impairment. SS typically presents as dry eyes (xerophthalmia) and dry mouth (xerostomia). This process can manifest either as the independent phenomenon of primary SS or as secondary SS when found in the context of another autoimmune process, most commonly rheumatoid arthritis or systemic lupus erythematosus. Nearly half of the patients with SS develop cutaneous manifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 37 publications
(117 reference statements)
0
30
0
3
Order By: Relevance
“…The primary clinical symptoms are those of sicca syndrome, including dry eyes (xerophthalmia) and mouth (xerostomia) [4]. Extraglandular cutaneous, pulmonary, gastrointestinal, cardiac, neurological, and renal symptoms may occur in SS patients [13,14,15,16,17]. Keratoconjunctivitis associated with dry eyes is a severe, extremely uncomfortable symptom of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…The primary clinical symptoms are those of sicca syndrome, including dry eyes (xerophthalmia) and mouth (xerostomia) [4]. Extraglandular cutaneous, pulmonary, gastrointestinal, cardiac, neurological, and renal symptoms may occur in SS patients [13,14,15,16,17]. Keratoconjunctivitis associated with dry eyes is a severe, extremely uncomfortable symptom of this disease.…”
Section: Discussionmentioning
confidence: 99%
“…[3] Sjögren's syndrome is an autoimmune connective disorder characterized by xerophthalmia and xerostomia due to lymphocytic infiltration of the lacrimal and salivary glands. [2] Earlier studies detected mitochondrial alterations in cells from these patients, which were related to the action of antimitochondrial autoantibodies. Recently, Perez et al, found that gene loci such as 1p34.2 (D1S3721), 3q13.31-q13.32 (D3S2460) were differentially expressed in labial salivary glands and epithelial cells in Sjögren's syndrome.…”
Section: Net Lettermentioning
confidence: 98%
“…[1] Sjögren's syndrome is a systemic autoimmune disease in which the exocrine glands are damaged by immune cells. [2] Herein, we describe a patient with the rare coexistence of Darier's disease and Sjögren's syndrome.…”
mentioning
confidence: 97%
“…The symptoms usually resolve with corticosteroids. Other skin manifestations include erythema nodosa, vitiligo, and digital ulcers (Kittridge et al, 2011).…”
Section: Cutaneous Featuresmentioning
confidence: 99%